Ecotoxicological effects of lanthanum in Mytilus galloprovincialis: biochemical and histopathological impacts - Pinto, João (2019)
Inappropriate processing and disposal of electronic waste contributes to the contamination of aquatic systems by various types of pollutants such as the rare-earth elements (REE) in which lanthanum (La) is included. Knowledge on the toxicity of these elements in marine organisms is still scarce when compared to other metals such as mercury (Hg) and arsenic (As). Therefore, this study aims to assess the toxicity of La on the mussel Mytilus galloprovincialis, considered a good bioindicator of aquatic pollution, through the analysis of metabolic, oxidative stress, neurotoxicity and histopathological markers. Organisms were exposed to different concentrations of La for a period of 28 days (0, 0.1, 1, 10 mg/L) under controlled temperature (18 °C ± 1.0) and salinity (30 ± 1) conditions. La concentrations in mussels increased in higher exposure concentrations. La exposure demonstrated a biochemical response in mussels, evidenced by lowered metabolism and accumulation of energy reserves, activation of the antioxidant defences SOD and GPx as well as the biotransformation enzymes GSTs, especially at intermediate concentrations. Despite oxidative stress being shown by a decrease in GSH/GSSG, oxidative damage was avoided as evidenced by lower LPO and PC levels. Inhibition of the enzyme AChE demonstrated the neurotoxicity of La in this species. Histopathological indices were significantly different from the control group, indicating impacts in gonads, gills and digestive glands of mussels due to La. These results show that La can be considered a risk for marine organisms and thus its discharge into the environment should be monitored.